Surgical Management of Skull Base Osteoradionecrosis in the Cancer Population – Treatment Outcomes and Predictors of Recurrence: A Case Series. (18th December 2021) - Habib, Ahmed; Hanasono, Matthew M; DeMonte, Franco; Haider, Ali; Breshears, Jonathan D; Nader, Marc-Elie; Gidley, Paul W; Su, Shirley Y; Hanna, Ehab Y; Raza, Shaan M
Graphical Abstract: